Assessing Employee Training Effectiveness: An Empirical Integration of Kirkpatrick Level 1 and Level 2 Evaluations - Frida Aprillia; Purwatiningsih Purwatiningsih; Dhuha Safria; Alan Budi Kusuma (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2026)
Training evaluations in DKI Jakarta's private sector are often limited to subjective participant satisfaction (Level 1) while neglecting objective learning outcomes (Level 2). This study evaluates a division's basic training program by integrating Kirkpatrick’s Level 1 (Reaction) and Level 2 (Learning). A quantitative descriptive approach was applied to 35 employees selected via purposive sampling. Data were collected through Likert-scale questionnaires and pre-test/post-test documentation, then analyzed using Excel and SPSS. Level 1 results showed positive responses, with facilitation method (T2=4.06) and material relevance (R1=4.03) scoring highest, while overall satisfaction (S1=3.49) scored lowest, highlighting a conflict between utility value and affective comfort due to daily workloads. At Level 2, a Paired Samples T-Test confirmed a highly significant surge in cognitive competence (t=-19.437, p=0.000), as the mean score rose from 39.00 to 76.86. The narrowing standard deviation (9.61 to 8.67) indicates a homogeneous equalization of knowledge. Management should alleviate daily workloads during training to boost affective satisfaction. Future research should expand longitudinally to encompass workplace behavior (Level 3) and organizational results (Level 4).